2018
DOI: 10.1016/j.jad.2018.05.079
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety symptoms are associated with prooxidant-antioxidant balance: A population-based study

Abstract: Symptoms of depression and anxiety appear to be associated with higher degrees of oxidative stress, expressed by higher serum PAB values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…Studies to date indicate that patients with depression have lower levels of antioxidative systems, and at the same time, they display an increased amount of oxidative stress markers when compared with healthy individuals (147,148). Some antioxidant therapeutics, like N-acetyl-cysteine, seem to show some effect in depression treatment (149).…”
Section: Oxidative Stress Depression and Curcuminmentioning
confidence: 99%
“…Studies to date indicate that patients with depression have lower levels of antioxidative systems, and at the same time, they display an increased amount of oxidative stress markers when compared with healthy individuals (147,148). Some antioxidant therapeutics, like N-acetyl-cysteine, seem to show some effect in depression treatment (149).…”
Section: Oxidative Stress Depression and Curcuminmentioning
confidence: 99%
“…In addition to endogenous oxidative stress, reasons of exogenous oxidative stress such as smoking, emotional stress, ultraviolet exposure, some chemicals, inflammation, pollution, and genetic defects activate and accelerate this process 4,12 . Psychological disorders such as anxiety and depression may play roles in the etiopathogenesis of PHG by increasing exogenous oxidative stress 17,31 . Akın Belli et al reported that emotional stress was higher in PHG 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Total oxidant status (TOS) and total antioxidant status (TAS) reflect global assessment of oxidative stress 15,16 . In addition, psychological disorders may increase oxidative stress 17 . In this study, we aimed to evaluate the oxidative stress status globally in PHG through measuring TOS and TAS in serum of individuals of PHG and emotional stress and anxiety levels.…”
Section: Introductionmentioning
confidence: 99%
“…The brain is especially susceptible to oxidative stress and antioxidants defend against the negative effects of oxidative stress in brain (Payne et al, 2012). Another underlying mechanism that may be responsible for this effect is that antioxidants have beneficial effects upon oxidative and inflammatory markers, which are often elevated during depression (Shafiee et al, 2017(Shafiee et al, , 2018Tayefi et al, 2017). A cohort study examined the relationship between high fruit and vegetable consumption and psychological behavior.…”
Section: Discussionmentioning
confidence: 99%